Prinsip Kehati-Hatian yang Dilakukan Notaris dalam Penyimpanan Minuta Akta Notaris - Ahmad Mukhlasul Abidin; Moh. Ali; Ainul Azizah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to examine the principles of caution used by notaries when storing minutes of notarial deeds. A notary is a public official who has the authority to make deed minutes and save them in the form of a notarial protocol. So far, notaries legally store deeds only in the form of notary protocols, there are no rules that clearly regulate the layout of storing deeds in the notary's office safely and with confidentiality maintained. Apart from that, the Notary must be able to guarantee legal certainty for the parties entering into a deed agreement by being given a copy of the deed and storing the minutes of the deed (original deed) safely. Notaries are expected to apply the principle of prudence with the deeds they make, the authority and obligations they have as a Notary. Bearing in mind the importance of Article 16 paragraph (1) letter b, which is the obligation of a Notary to make a deed and save it in a Notary Protocol. This research uses normative juridical research with data collection techniques from literature consisting of primary legal and secondary legal materials.